Investigation of the Role of Oxidative Stress-Related Genetic Variants in Type 2 Diabetes Mellitus-associated Nephropathy - Begum, Farhana; Lakshmanan, Karpagavel (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
The present study investigates the role of oxidative stress-related genetic variants in type 2 diabetes mellitus-associated nephropathy. Type 2 diabetes is thought to be associated with microvascular complications that comprise retinopathy, nephropathy, and neuropathy. Oxidative stress is a predominant factor involved in the pathogenesis of DN and alters metabolic endeavour and its hemodynamic pathways, which have varied correlations with renal problems, one of which is diabetic nephropathy, which leads to end-stage renal disease. Renal injury in DN occurs primarily through oxidative stress, which disrupts metabolic and hemodynamic pathways. Hyperglycemia is regarded as a hallmark feature of diabetes that increases reactive oxygen species generation, which eventually leads to increased oxidative stress, and this is considered the most essential event in the onset of DN. To prevent tubular injury in DN, antioxidants can be used to combat oxidative stress, which is primarily caused by several pathways. The most significant antioxidative enzymes are superoxide dismutase, catalase, glutathione-S-transferase, and glutathione peroxidase. As a result, this chapter emphasizes antioxidant gene polymorphisms and hypothesizes that these antioxidant genes may be an essential component of DN pathogenesis. Moreover, this chapter also retorts to the research questions raised by the physicians and illustrates the importance of regional population studies on detecting the SNPs of antioxidant genes and targeting therapeutic approaches aiding to lessen the severity of the disease at its initial stages.